The Effects of the Physical Setting on Students’ Listening Comprehension - Ameen, Bahzad; Saeed A. Saeed (International Journal of Language and Literary Studies, 2022)
Since the physical setting in the listening comprehension process has been proven to be one of the troublesome issues for EFL learners, The current study looks into the possibility that the physical environment impacts students’ listening comprehension process. The study aims to find out problems with hearing due to the physical environment. To do this, a questionnaire survey was prepared to serve the aim of the study. The sample of this study consists of 87 participants. Eighteen males and sixty-nine females from 2nd year English department students of the College of Basic Education, University of Duhok, took part in the study. The results of this study show that due to a noisy physical setting (or learning environment) and listening aids, materials, or equipment with volume or sound quality issues, students frequently or often have difficulty listening to aurally presented texts. Finally, according to the literature review, the current study’s findings are consistent with those of other studies.